2008
DOI: 10.1177/089686080802800508
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Outcomes between Diabetic and Nondiabetic Capd Patients in India

Abstract: Background Continuous ambulatory peritoneal dialysis (CAPD) has been an established modality of renal replacement therapy in India for a decade, but there is a paucity of published data on the outcome of CAPD patients in India. We analyzed our data to determine the overall predictors of survival and compared patient survival between diabetic and nondiabetic end-stage renal disease patients on CAPD. Methods Of 373 patients, 197 were diabetic (165 males, 32 females) and 176 nondiabetic (104 males, 72 females). P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
24
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 26 publications
5
24
4
Order By: Relevance
“…We found diabetes to be an important risk factor affecting the prognosis of PD patients. Our findings are consistent with previous studies 32 , 36 . It has been reported that PD patients with diabetes have a 30% increased risk of death, compared to non-diabetic patients 37 .…”
Section: Discussionsupporting
confidence: 94%
“…We found diabetes to be an important risk factor affecting the prognosis of PD patients. Our findings are consistent with previous studies 32 , 36 . It has been reported that PD patients with diabetes have a 30% increased risk of death, compared to non-diabetic patients 37 .…”
Section: Discussionsupporting
confidence: 94%
“…However, publications regarding MS in non-diabetic patients are few 23,29 despite the fact that PD is an established mode of renal replacement therapy and almost half of the ESRD patients who opt for PD are non-diabetic. 18 We have shown in the present study that the patient and technique survival of non-diabetic PD with MS are significantly inferior compared to that of patients without MS. Similar to our study, Li et al 29 and Park et al 23 have also shown that patients with MS have worse survival than those of patients without MS. Park et al did not find any individual components of MS as a predictor of mortality while they found MS as a whole an important predictor of mortality.…”
Section: Discussionmentioning
confidence: 44%
“…Contrary to this we have previously reported that age, nutritional status on SGA and peritonitis are the risk factors of mortality in PD patients. 18,44 These observational differences may also be because of the exclusion of diabetic PD patients from the present study. The prevalence of MS increases with age in the general population.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations